THE EFFECTS OF DELISTING ON MARKET LIQUIDITY: AN ANALYSIS OF THE ASEAN – 5 STOCK MARKETS - Yusoff , Mohd Yushairi Mat; Hashim, Mohamad Syafiqi; Salim, Mahfuzah; Ismail, Nur Hafizah (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the delisting effects on market liquidity within the ASEAN – 5 countries. By using traditional panel estimation for the 1990 – 2014 period, the results of the Random Effects Model (REM) suggest that delisted companies to have a negative effect on market liquidity. Also, the results signify that economic growth or a country’s income is statistically significant in determining the changes in market liquidity across the ASEAN – 5 countries. Therefore, the policy makers are recommended to constantly review the severity of delisting effects on the domestic market liquidity and implement necessary measures that can bolster the investors’ confidence towards ascertaining the sustainable levels of market liquidity within the ASEAN – 5 countries over the short and long terms.